"I'm a Visual Learner so I like this": Investigating Student and Faculty Tutorial Preferences. Issue 4 (2nd October 2017) - Lantz, Catherine; Insua, Glenda M.; Armstrong, Annie; Dror, David; Wood, Tara
ABSTRACT: Online tutorials are useful for reinforcing information literacy concepts addressed in library instruction. A wide range of tutorial types cater to different learning styles and feature varying levels of interactivity. In this study, students and faculty reported experiences using two types of tutorials teaching basic search strategies—an interactive tutorial, and a video tutorial. Although both groups favored the video, faculty were split about which tutorial they would rather assign, a discrepancy suggesting questions about how tutorial developers should balance user preferences with learning needs. These findings provide valuable insights for librarians and instructional designers considering creating information literacy tutorials.